JASPer controls interphase histone H3S10 phosphorylation by chromosomal kinase JIL-1 in Drosophila - Christian Albig (Nature Portfolio, 2019)
The chromosomal kinase JIL-1 is responsible for interphase histone H3S10 phosphorylation and has been proposed to protect active chromatin from heterochromatinisation. Here, the authors show that JIL-1 is stabilized and anchored to active genes and telomeric transposons by JASPer, which binds to H3K36me3 nucleosomes via its PWWP domain.